Phytochemical Investigation and Neuropharmacological Activity of Stem Extracts of Gynocardia Odorata R.Br. (Chittagong University Journal of Biological Sciences, 2024)
From the stem part of Gynocardiaodorata R.Br. the presence of steroids,alkaloids,saponins, tannins,flavonoids etc. has been indicated through phytochemical screening.The crude extract was prepared with absolute methanol and later on pet ether, chloroform, n-hexane and carbon tetrachloride were used as solvents to prepare soluble fractions. Neuropharmacological effect was investigated by open field,hole cross,hole board and elevated plus maze test forscreening CNS depressant and anxiogenic effect on Swiss albino mice and compared with Diazepam as a reference standard. The hole board method showed dose-dependent significant decrease in the number of head dipping (P